Changes in the regional homogeneity of resting-state magnetic resonance imaging in perimenopausal women - Min Liu; Hui Yang; Jian Qin; Qianqian Yao; Guihua Yang; Jiang Li (BMC, 2021)
Abstract Background There is a noticeable lack of systematic researches on evaluating the correlation between serum estrogen levels and changes in brain functional areas of perimenopausal women.The aim of this study is to investigate the regional spontaneous brain activity changes in perimenopausal women. Methods Based on the resting-state functional magnetic resonance imaging datasets acquired from 25 perimenopausal women and 20 healthy women of reproductive age, a two-sample t-test was performed on individual normalized regional homogeneity (ReHo) maps. Relationships between abnormal ReHo values and the self-rating anxiety scale (SAS), the self-rating depression scale (SDS) were investigated with Pearson correlation analysis. We also investigated the correlation between abnormal ReHo values and serum estrogen level. Results In the perimenopausal group, we found increased ReHo in the right posterior cerebellum (region 2), left middle frontal gyrus and left middle cingulate gyrus ( $$P<0.05$$ P < 0.05 ). Additionally, the ReHo values in left middle frontal gyrus and leftt middle cingulate gyrus showed positively significant correlation with the SAS, SDS scores. On the contrary, there was no significant correlation between the ReHo value in right posterior cerebellum and SDS, SAS scores. In the perimenopausal group, the ReHo values in the left middle frontal gyrus and left middle cingulate gyrus were negatively correlated with the serum estrogen level ( $$P<0.05$$ P < 0.05 ). Conclusion The results of this preliminary study have suggested that abnormal spontaneous activities of multiple brain regions during resting state was already altered in perimenopausal women. Alterative activities might be related to emotional regulation deficits and cognitive impairment, and might potentially represent the neural mechanism underlying perimenopausal period.